Tantangan dan Solusi dalam Pengelolaan Dana BOS di Sekolah Dasar - Hida, Ester Uru; Prateila, Chrisma; Pukada, Michael Alan Hirdi; Djami, Denanda Isti Novalia (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik, 2025)
The School Operational Assistance Fund (BOS) program is a strategic initiative of the Indonesian government to support education financing in the 12-year compulsory education program. This program aims to eliminate school operational fees, especially for students in private schools, and improve access to and quality of education. However, its implementation still faces various challenges, such as lack of transparency, limited managerial capabilities of school principals, and budget allocations that are not in accordance with the provisions. This study focuses on identifying challenges and solutions related to the management of BOS Funds at SDN Karangtengah 01 using a qualitative descriptive approach. Data were collected through interviews, observations, and document analysis, with data validity strengthened through triangulation. The results of the study indicate positive practices, such as the preparation of detailed RKAS and transparency efforts through financial information boards. However, obstacles such as late disbursement of funds, weak internal supervision, and inefficient manual management are still obstacles. The proposed solutions include increasing human resource capacity, strengthening the monitoring system, and implementing digital technology in financial recording. This study makes an important contribution to increasing accountability and efficiency in the management of BOS Funds, as well as being a reference for developing more responsive and effective education policies.